Morphology of the Urban Phenomenon and Its Relation with Urban Livability - Shahbazi, Samaneh; Nematollahi , Mohamadali; Nabian, Nashid (International Journal of Architectural Engineering Technology, 2023)
The livability of a city is a crucial aspect that greatly influences the well-being of its residents, and its relationship with the city's morphology is significant. This study aims to examine the correlation between block livability and block form. In the first step, the goal is to propose a quantitative model, the "Livable Block Index (LBI)," to measure the level of livability. The LBI considers the multi-functionality of urban zones as a key factor in measuring block livability, analyzing both the variety of uses within each lot and the distribution of uses across the block. Additionally, the study investigates the form of urban blocks, considering their area, shape, and proportions. The proposed model is applied to specific districts in Tehran, using Grasshopper for data modeling, visualization, and analysis. Initial findings reveal a meaningful relationship between block form and livability levels; however, it is apparent that a comprehensive understanding requires the consideration of additional parameters. Further research is necessary to develop a more comprehensive view of the correlations between urban block form and livability.